Limited sensitivity analysis of ARAIM availability for LPV-200 over Australia using real data - El-Mowafy, Ahmed; Yang, C. (2015)
Current availability of Advanced Receiver Autonomous Integrity Monitoring (ARAIM) for LPV-200 in aviation is experimentally investigated using real navigation data and GPS measurements collected at 60 stations across Australia. ARAIM algorithm and fault probabilities were first discussed. Availability sensitivity analysis due to changes in the elevation mask angle and the error model parameters URA, URE, and nominal biases for integrity and accuracy used for computation of the protection level is presented. It is shown that incorporation of other GNSS constellation with GPS in ARAIM is needed to achieve LPV-200 Australia wide. The inclusion of BeiDou with GPS at two tests sites in Western and Eastern Australia demonstrates the promising potential of achieving this goal.